RAM‐SCB simulations of electron transport and plasma wave scattering during the October 2012 “double‐dip” storm - Jordanova, V. K.; Tu, W.; Chen, Y.; Morley, S. K.; Panaitescu, A.‐D.; Reeves, G. D.; Kletzing, C. A. (Journal of geophysical research. Space physics, 2016)
Mechanisms for electron injection, trapping, and loss in the near‐Earth space environment are investigated during the October 2012 “double‐dip” storm using our ring current‐atmosphere interactions model with self‐consistent magnetic field (RAM‐SCB). Pitch angle and energy scattering are included for the first time in RAM‐SCB using L and magnetic local time (MLT)‐dependent event‐specific chorus wave models inferred from NOAA Polar‐orbiting Operational Environmental Satellites (POES) and Van Allen Probes Electric and Magnetic Field Instrument Suite and Integrated Science observations. The dynamics of the source (approximately tens of keV) and seed (approximately hundreds of keV) populations of the radiation belts simulated with RAM‐SCB is compared with Van Allen Probes Magnetic Electron Ion Spectrometer observations in the morning sector and with measurements from NOAA 15 satellite in the predawn and afternoon MLT sectors. We find that although the low‐energy (E< 100 keV) electron fluxes are in good agreement with observations, increasing significantly by magnetospheric convection during both SYM‐H dips while decreasing during the intermediate recovery phase, the injection of high‐energy electrons is underestimated by this mechanism throughout the storm. Local acceleration by chorus waves intensifies the electron fluxes at E≥50 keV considerably, and RAM‐SCB simulations overestimate the observed trapped fluxes by more than an order of magnitude; the precipitating fluxes simulated with RAM‐SCB are weaker, and their temporal and spatial evolutions agree well with POES/Medium Energy Proton and Electron Detectors data. Key Points First RAM‐SCB simulations with 2‐D (MLT‐ and L‐dependent) event‐specific chorus wave models inferred from LEO and RBSP data The measured low‐energy trapped and precipitating electron fluxes are well reproduced by magnetospheric convection Local acceleration by chorus waves intensifies the electron fluxes at energies E greater than approximately 50 keV and overestimates observations